2022
DOI: 10.3390/ijerph19169944
|View full text |Cite
|
Sign up to set email alerts
|

Doctor Clerk Implementation in Rural Community Hospitals for Effective Task Shifting of Doctors: A Grounded Theory Approach

Abstract: With the diversification of medical care and work reform, doctor clerks play a major role today and are recruited to mitigate the burden of doctors worldwide. Their recruitment can improve the working conditions of physicians, facilitate task shifting in rural community hospitals, improve patient care, and help address the lack of healthcare resources. This study used a qualitative method to investigate difficulties in the implementation of doctor clerks and ascertain the features of effective implementation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Regarding effectiveness in task shifting and workload reduction of physicians, the predominance of document support as the primary task among doctor clerks (94.1%) aligns with the initial intent of their role to alleviate the administrative burden on physicians [28]. This task shifting is evident in the reduced paperwork time and physician overtime work, as reported in several studies [18,21,27]. Expanding roles to include consultation and ordering support also signifies the evolving nature of the doctor clerk's responsibilities, potentially leading to a more holistic approach to assisting physicians [26,27].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Regarding effectiveness in task shifting and workload reduction of physicians, the predominance of document support as the primary task among doctor clerks (94.1%) aligns with the initial intent of their role to alleviate the administrative burden on physicians [28]. This task shifting is evident in the reduced paperwork time and physician overtime work, as reported in several studies [18,21,27]. Expanding roles to include consultation and ordering support also signifies the evolving nature of the doctor clerk's responsibilities, potentially leading to a more holistic approach to assisting physicians [26,27].…”
Section: Discussionmentioning
confidence: 70%
“…This task shifting is evident in the reduced paperwork time and physician overtime work, as reported in several studies [18,21,27]. Expanding roles to include consultation and ordering support also signifies the evolving nature of the doctor clerk's responsibilities, potentially leading to a more holistic approach to assisting physicians [26,27]. Doctor clerks can be involved in health promotion, vaccination, and primary to tertiary prevention for better quality patient care [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous studies have considered the facilitating role of specialists (e.g., dietitians or general practitioners) in guiding patients to healthy diets [ [36] , [37] , [38] , [39] , [40] , [42] , [43] , [44] , [45] , 55 ], but we found that some “specialists” could be a barrier to intervention implementation for not being able to give adequate and effective guidance promptly if they lacked sufficient competence, played weak roles or the intervention stopped abruptly. This is particularly pronounced in primary care settings where healthcare resources are relatively scarce [ 38 , 39 , 68 ], which puts higher demands on the adequacy, professionalism and timeliness of interventionists. Furthermore, we found that the level of intervention is important.…”
Section: Discussionmentioning
confidence: 99%